Energy and sustainability at Fort Hays State University - Adams, Paul (Kansas State University, 2010)
Kansas is the third windiest state in the nation and is centrally situated geographically for providing access to commercialized wind energy. Kansas wind could be a major contributor to an energy future for the United States that is renewable, efficient, and home-grown. Yet, there are many steps to go from here to there. This panel will feature experts in wind energy technologies and development from around Kansas. They will discuss some of the technical hurdles and workforce needs if this development is to take place. They will also discuss the potential role of higher education partnerships across Kansas in fully developing our wind resource for the benefit of all Kansans.
Keywords: Sustainability; Wind energy; Education; Curriculum; Partnerships